The Therapeutic Effect of Endoscopic Tumor Resection on Acromegalic Cardiomegaly in Patients With Pituitary Adenoma - Ebrahimzadeh, Kaveh; Mojtabavi, Kurosh; Mohammadi, Sasan; Farahani, Mehrdad; Gholizadeh Ghozloujeh, Zohreh; Asaadi, Sina; Sharifi, Guive; Joshaghanian, Mohammad Amin; Rezaei, Omidvar (International Clinical Neuroscience Journal, 2019)
Background: Acromegaly defines as chronic elevations of insulin-like growth factor-1 (IGF-1) and growth hormone (GH), which results in enlargement of organs and soft tissues. Cardiovascular complications of acromegaly such as cardiomegaly, hypertension contributing to a high risk of cardiovascular events. This study aimed to identify the determinants of the prevalence of cardiomegaly as cardiovascular comorbidity of acromegaly and the potential effect of the curative intervention. Methods: A total of 160 patients with acromegaly due to pituitary adenoma participated in this study. Acromegaly diagnosed was based on clinical manifestations, age-adjusted plasma IGF-I, and elevated plasma GH levels, not suppressible during an oral glucose tolerance test (75 g). Electrocardiogram and chest X-ray obtained in all patients. Treatment approaches included transsphenoidal surgery and hormonal evaluation performed before and six months after surgery. Results: The GH serum level was elevated in all patients before surgery, with a mean of 33.7 ng/mL that reached 5.7 ng/mL after surgery. Mean IGF-1 was 794.1 ng/mL that reached 395.6 ng/mL postoperatively. The prevalence of cardiomegaly was 15% that improved in 5% of patients after trans sphenoidal surgery. Conclusion: Appropriate surgical intervention in acromegaly that complicated by cardiomegaly may result in significant improvement of the cardiac structure.